(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Identity expression can be seen at either a personal or a social level. It can be shown in several ways, particularly through poetry. Therefore, this paper seeks to examine how identity is expressed modally in Darwish’s famous poem “Identity Card”. Leech’s (1974) theory of “seven types of meaning” is used as the theoretical framework for the study. As the study aims to figure out how modality is constructed when expressing identity in the poem, this linguistic norm has been used to track the mood and attitude of the poets in the composition of the stanzas. The findings of the study revealed that identity is expressed modally in the sensations that Mahmoud Darwish carries for the Palestinian, Arab, National, Cultural, Geographical and Historical identities. His language enacted the way he feels towards these six components of his belongings. Nationalism is seen as an important perspective in the affiliations of Darwish. The national identity is, however, the central concept of the poem. The modality provides a rough picture of what is going on in his mind as he experiencing the loss of land. It also comes in harmony with the general cultural context that contributes to his poetic experiences.